Numerical analyses of the interrelation between extracellular smooth muscle orientation and intracellular filament overlap in the human abdominal aorta. Issue 12 (11th October 2018) - Haspinger, Daniel Ch.; Murtada, Sae‐Il; Niestrawska, Justyna A.; Holzapfel, Gerhard A.
Abstract: Smooth muscle cells are one of the functional constituents in the human abdominal aorta, located in the medial layer, forming two helices similar to collagen fibers. During development, angiogenesis and vascular remodeling, smooth muscle cells experience changes in their orientation and a reorganization of their intracellular filament structure. In order to study the so far not so well‐known interrelation between smooth muscle orientation and the intracellular filament structure in the human abdominal aorta a recently proposed mechanochemical model is modified. Two families of muscle fibers are introduced with a non‐symmetric filament overlap behavior, and the model is implemented into a finite element code. Active material parameters are obtained by fitting the model behavior to experimental data. Fitting results highlight that the non‐symmetry of the filament overlap behavior depends on the muscle fiber orientation. Modification of the smooth muscle orientations and the intracellular filament structure, and their influences on the human abdominal aortic responses are investigated using a finite element model of an aortic ring. We show how changes in the aortic wall behavior due to alterations in the smooth muscle orientation can be reduced, and even prevented by adjusting the filament overlap behavior. Thus, a modification of the intracellular filament structure could be used as a therapeutic approach in response to pathological vascular adaptation processes where changes in smooth muscle orientation are involved. Abstract : Smooth muscle cells are one of the functional constituents in the human abdominal aorta, located in the medial layer, forming two helices similar to collagen fibers. During development, angiogenesis and vascular remodeling, smooth muscle cells experience changes in their orientation and a reorganization of their intracellular filament structure. In order to study the so far not so well‐known interrelation between smooth muscle orientation and the intracellular filament structure in the human abdominal aorta a recently proposed mechanochemical model is modified. Two families of muscle fibers are introduced with a non‐symmetric filament overlap behavior, and the model is implemented into a finite element code. Active material parameters are obtained by fitting the model behavior to experimental data. Fitting results highlight that the non‐symmetry of the filament overlap behavior depends on the muscle fiber orientation. Modification of the smooth muscle orientations and the intracellular filament structure, and their influences on the human abdominal aortic responses are investigated using a finite element model of an aortic ring. We show how changes in the aortic wall behavior due to alterations in the smooth muscle orientation can be reduced, and even prevented by adjusting the filament overlap behavior. Thus, a modification of the intracellular filament structure could be used as a therapeutic approach in response to pathological vascular adaptation processes where changes in smooth muscle orientation are involved.